(untitled) (Bangladesh Journal of Otorhinolaryngology, 2019)
Background: Cancer continues to be a major health problem despite advances in medical technology for its diagnosis and treatment. Cancer of the larynx is the eleventh most common cancer in the world. Carcinoma larynx is a multifactorial disease. Smoking, betel-nut, betel-leaf chewing habit and drinking alcohol are the most important factors associated with carcinoma larynx. Objective: To detect the rate and level of cervical lymph node metastasis in laryngeal carcinoma Methods: Detailed information was obtained in each cases according to protocol. Complete history was taken from accompanying attendants. Thorough clinical examination was done. All the information’s were recorded in the fixed protocol. Patients were randomly assigned to one of three groups by card sampling. Collected data were classified, edited, coded and entered into the computer for statistical analysis by using updated computerized program SPSS-19 Results: Out of 50 cases the mean average age was found 58.5±11.9 years with range from 39 to 78 years. Majority (70.0%) patients presented with supraglottic carcinoma followed by 13(26.0%) glottic carcinoma and 2(4.0%) subglottic carcinoma. More than three fourth (78.0%) patients had difficulty in swallowing followed by 17(34.0%) had hoarseness of voice, 12(24.0%) had discomfort in throat, 10(20.0%) had earache, 6(12.0%) had hemoptysis and 4(8.0%) had cough. Majority (42.0%) patients were found N0 followed by 15(30.0%) N1, 13(26.0%) N2 and 1(2.0%) N3 of neck node. Majority (42.0%) patients was found in stage T3 followed by 7(14.0%) in stage T1, 18(36.0%) in stage T2 and 4(8.0%) in stage T4. Majority (56.0%) patients was found in level-II of neck nodes followed by 12(24.0%) level III, 4(8.0%) level IV, 3(6.0%) level II+III, 2(4.0%) level III+IV and 1(2.0%) level III+IV+V of neck nodes. Conclusion: Laryngeal carcinoma is a common clinical entity in otolaryngology practice. Male were more predominant and the highest age group was 51-60 years. In our study most common Laryngeal carcinoma was supraglottic in nature. T3 was the commonest stage of involvement. Common clinical presentation was difficulty in swallowing and hoarseness of voice. N 0 and N1 was the most common pattern of neck node metastasis. In our series majority of them were in level II Bangladesh J of Otorhinolaryngology; October 2018; 24(2): 115-124